An event-triggered observation scheme for systems with perturbations and data rate constraints - Voortman, Quentin; Efimov, Denis; Pogromsky, Alexander Yu; Richard, Jean-Pierre; Nijmeijer, Henk (Automatica (Oxford), 2022)
In this paper, an event-triggered observation scheme is considered for a perturbed nonlinear dynamical system connected to a remote location via a communication channel, which can only transmit a limited amount of data per unit of time. The dynamical system, which is supposed to be globally Lipschitz, is subject to bounded state perturbations. Moreover, at the system’s location, the output is measured with some bounded errors. The objective is to calculate estimates of the state at the remote location in real-time with maximum given error, whilst using the communication channel as little as possible. An event-triggered communication strategy is proposed in order to reduce the average number of communications. An important feature of this strategy is to provide an estimation of the relation between the observation error and the communication rate. The observation scheme’s efficiency is demonstrated through simulations of unicycle-type robots.